EFEKTIVITAS DAUN JAMBU BIJI DALAM MENGATASI DIARE - Ida Bagus Laksamana Vivekananda (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
The most common digestive tract disorders are diarrhea and constipation. Diarrhea is a disease characterized by a change in stool consistency (to become liquid) accompanied by an increase in the frequency of defecation more than 3 times a day accompanied by changes with or without blood and/or mucus. Diarrhea is the most common cause of morbidity and mortality as well as malnutrition in children, especially in developing countries. Plants that are efficacious in overcoming diarrhea is guava. Guava leaf extract contains phytochemicals which are known to have pharmacological activity showing high levels of tannins and flavonoids and may be responsible for the anti-diarrhea activity. The purpose of this article review is to determine the potential effectiveness of guava leaves in treating diarrhea. The method used in making this article review is literature study by accessing national and international journals. The conclusion obtained is based on the results of the analysis of several articles, namely guava leaves are effective in treating diarrhea.